“What is right and real – is the storytelling”: masculinity, media and creativity - Aharoni Lir, Shlomit; Ayalon, Liat (Creativity Studies, 2022)
The stereotypical view of creativity as an emblem of youth, and old age as a signifier of decline can hold grave consequences for filmmakers in the second half of life, as this misconception can result in negative attitudes, a decline in media coverage, and less funding for film production. Thus, ageing male film directors might face a collisional intersection, when the gender-based status that provides social privileges, meets with older age-based status, which leads to social weakening. This qualitative study explored the means which male directors in the second half of life use to remain creative and make films in an ageist, vastly changing world. The study is based on a dataset of transcribed semi-structured interviews with 13 well-known Israeli male directors over the age of 55. The findings led to the formation of a model of creativity in older age, which consists of the following six pathways: inspiration, adaptation, innovation, preservation, circumvention and imagination. While some of the interviewed directors emphasized their ability to change and adapt to the new cinematic world, others adhered to their old filmmaking language. The understanding of the cinematic creation as based upon the art of storytelling was common among both “camps”.